PERAN INFLUENCER MARKETING TERHADAP KEPUTUSAN PEMBELIAN: PENDEKATAN TINJAUAN LITERATUR SISTEMATIS - Kartika, Winda (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This study aims to examine the role of influencer marketing in consumer purchasing decisions through a systematic literature review approach. In the digital era, marketing strategies have undergone significant transformation, where the influence of social media figures plays a crucial role in shaping consumer perception and behavior. Based on the analysis of 20 selected academic journals published between 2020 and 2025, the findings indicate that influencer marketing significantly contributes to building trust, increasing brand awareness, and influencing both purchase intention and decision-making processes. The effectiveness of this strategy is highly dependent on the influencer’s credibility, alignment with the target market, and the quality of engagement with their audience. However, several challenges such as engagement manipulation, reputational risks, and improper influencer selection may hinder campaign success. When implemented ethically and strategically, influencer marketing presents a powerful and sustainable tool in enhancing digital marketing performance and driving consumer behavior